Cytotoxicity and 1H NMR metabolomics analyses of microalgal extracts for synergistic application with Tamoxifen on breast cancer cells with reduced toxicity against Vero cells. Issue 3 (March 2022) - Hussein, Hanaa Ali; Kassim, Murni Nur Islamiah; Maulidiani, M.; Abas, Faridah; Abdullah, Mohd Azmuddin
Abstract: This study evaluated the cytotoxic activity of Tamoxifen (TMX), an anti-estrogen drug, with microalgal crude extracts (MCEs) in single and synergistic application (TMX-MCEs) on MCF-7 and 4T1 breast cancer cells, and non-cancerous Vero cells. The MCEs of Nannochloropsis oculata, Tetraselmis suecica and Chlorella sp. from five different solvents (methanol, MET; ethanol, ETH; water, W; chloroform, CHL; and hexane, HEX) were developed. The TMX-MCEs-ETH and W at the 1:2 and 1:3 ratios, attained IC50 of 15.84–29.51 μg/mL against MCF-7; 13.8–31.62 μg/mL against 4T1; and 24.54–85.11 μg/mL against Vero cells. Higher late apoptosis was exhibited against MCF-7 by the TMX- N. oculata -ETH (41.15 %); and by the TMX- T. suecica -ETH (65.69 %) against 4T1 cells. The TMX- T. suecica -ETH also showed higher ADP/ATP ratios, but comparable Caspase activities to control. For Vero cells, overall apoptotic effects were lowered with synergistic application, and only early apoptosis was higher with TMX- T. suecica -ETH but at lower levels (29.84 %). The MCEs-W showed the presence of alanine, oleic acid, linoleic acid, lactic acid, and fumaric acid. Based on Principal Component Analysis (PCA), the spectral signals for polar solvents such as MET and ETH, were found in the same cluster, while the non-polar solvent CHL was with HEX, suggesting similar chemical profiles clustered for the same polarity. The CHL and HEX were more effective with N. oculata and T. suecica which were of the marine origin, while the ETH and MET were more effective with Chlorella sp., which was of the freshwater origin. The synergistic application of microalgal bioactive compounds with TMX can maintain the cytotoxicity against breast cancer cells whilst reducing the toxicity against non-cancerous Vero cells. These findings will benefit the biopharmaceutical, and functional and healthy food industries. Abstract : Cytotoxicity; 1 H NMR metabolomics; Tamoxifen; Microalgal extracts; Synergistic application.